Heterointegration of Pt/Si/Ag Nanowire Photodiodes and Their Photocatalytic Properties - Qu, Yongquan (2010)
Photocatalyst mediated photoelectrochemical processes can make use of the photogenerated electrons and holes onsite for photocatalytic redox reactions, and enable the harness and conversion of solar energy into chemical energy, in analogy to natural photosynthesis. However, the photocatalysts available to date are limited by either poor efficiency in the visible light range or insufficient photoelectrochemical stability. We show that a Pt/Si/Ag nanowire heterostructure can be rationally synthesized to integrate a nanoscale metal-semiconductor Schottky diode encased in a protective insulating shell with two exposed metal catalysts. The synthesis of Pt/Si/Ag nanowire diodes involves a scalable process including the formation of silicon nanowire array through wet chemical etching, electrodeposition of platinum and photoreduction of silver. We further demonstrated that the Pt/Si/Ag diodes exhibited highly efficient photocatalytic activity for a wide range of applications including environmental remediation and solar fuel production in the visible range. In this article, photodegradation of indigo carmine and 4-nitrophenol were used to evaluate the photoactivity of Pt/Si/Ag diodes. The Pt/Si/Ag diodes also show high activity for photoconversion of formic acid into carbon dioxide and hydrogen.